2018
DOI: 10.1186/s13104-018-3946-9
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between raw and predicted mortality in a paediatric intensive care unit in South Africa

Abstract: ObjectivePaediatric intensive care resources are limited in sub-Saharan Africa. The mortality rate in a combined Paediatric/Neonatal Intensive Care Unit in Johannesburg, South Africa was almost double that in a dedicated paediatric intensive care unit in the same country. This study aimed to compare the raw mortality rate with that predicted with the Paediatric Index of Mortality (version 3), by doing a retrospective analysis of an existing database.ResultsA total of 530 patients admitted to the intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Mortality rates reported in developing countries varied from 9.8-35%, often these patients arrived late with multiple complications leading to death despite the best available therapy [17]. In the present study, the mortality rate was 26.7%, which come in line with Ballot et al, [18] study in South Africa done from January 2015 to December 2017 showed that mortality rate was 27.1% and with Grippa et al, [15]study with 27.8% mortality. However in the study by Valavi et al, [19], The mean duration of hospitalization was 3.3 (SD = 3.7) days.…”
Section: Discussionsupporting
confidence: 89%
“…Mortality rates reported in developing countries varied from 9.8-35%, often these patients arrived late with multiple complications leading to death despite the best available therapy [17]. In the present study, the mortality rate was 26.7%, which come in line with Ballot et al, [18] study in South Africa done from January 2015 to December 2017 showed that mortality rate was 27.1% and with Grippa et al, [15]study with 27.8% mortality. However in the study by Valavi et al, [19], The mean duration of hospitalization was 3.3 (SD = 3.7) days.…”
Section: Discussionsupporting
confidence: 89%
“…L a i m p l e m e n t a c i ó n d e l a s e s c a l a s d e mortalidad permite evaluar la calidad en la atención de niños que ingresan a las UCIP, [11][12][13][14] por lo que es pertinente realizar estudios multicéntricos que permitan una muestra más robusta y resultados precisos. Las limitaciones de este estudio son el reducido número de pacientes y su realización en un solo centro hospitalario.…”
Section: Discussionunclassified
“…The implementation of mortality scales allows to assess the quality of care of children admitted to the PICU, [11][12][13][14] so it is relevant to carry out multicenter studies that include a more robust sample and allow to obtain accurate results. The limitations of this study are the small number of patients and the fact that it was carried out in a single hospital.…”
Section: Discussionmentioning
confidence: 99%